2005
DOI: 10.1111/j.1471-0528.2005.00638.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of mifepristone in combination with misoprostol administered sublingually or vaginally for medical abortion up to 13 weeks of gestation

Abstract: Objective To assess women's acceptability, the efficacy and side effects of sublingual versus vaginal administration of misoprostol in combination with mifepristone for medical abortion up to 13 weeks of gestation. Design Randomised controlled trial.Setting Aberdeen Royal Infirmary.Population Women undergoing medical abortion under the terms of the 1967 Abortion Act.Methods Mifepristone (200 mg) was given orally followed 36 -48 hours later by misoprostol administration (sublingual: 600 Ag; vaginal: 800 Ag). A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 20 publications
(29 reference statements)
2
40
0
4
Order By: Relevance
“…When judged by the efficacy of medical termination in the early part of the first trimester our results are comparable with previous publications [6] [17] [18]. When compared with previous studies of late first semester medical TOPs, the overall complete abortion rate was close to the success rates reported in previous studies [13] [14] [19].…”
Section: Discussionsupporting
confidence: 81%
“…When judged by the efficacy of medical termination in the early part of the first trimester our results are comparable with previous publications [6] [17] [18]. When compared with previous studies of late first semester medical TOPs, the overall complete abortion rate was close to the success rates reported in previous studies [13] [14] [19].…”
Section: Discussionsupporting
confidence: 81%
“…Studies have explored the effectiveness of medical termination of pregnancy after 10 weeks from LMP, and have demonstrated the efficacy and acceptability of regimens of mifepristone and misoprostol. [5][6][7][8][9] Most protocols used for gestational ages above 63 days from LMP require 800 lg vaginal misoprostol in an in-clinic setting, 24-48 hours after the administration of 200 mg mifepristone, with an additional 400 lg vaginal, oral or sublingual misoprostol administered every 3 hours. As clinical research shows, the effectiveness of termination of pregnancy with mifepristone-misoprostol does not suddenly cease at 64 days of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Termination of pregnancy with mifepristonemisoprostol is also used in the late first trimester (10)(11)(12) weeks from LMP) with documented success rates after 9 weeks from LMP being comparable with those achieved at earlier gestations, with some modifications in the protocol. [5][6][7][8][9][10] Previous research has indicated a high correlation between pregnancy dating determined by clinician (based on bimanual examination and history) and that determined by sonography. 11 Women who have a clear idea of the date of their LMP tend, on average, to believe that their pregnancies are slightly more advanced than they are.…”
Section: Introductionmentioning
confidence: 99%
“…Cochrane review considers that use of misoprostol will reduce the need for mechanical dilatation to between 14 and 39% [1]. Sublingual misoprostol was able to achieve the highest serum peak concentration compared to the oral and vaginal routes, and it is more comfortable for those wishing to avoid vaginal administration [11,12]. …”
Section: Discussionmentioning
confidence: 99%